From Senegal to Augsburg: Gum Arabic and the Central European Textile Industry in the Eighteenth Century. (2nd January 2019) - Wimmler, Jutta
Abstract : West Africa's role in the early modern economy is usually reduced to that of a supplier of forced labour for American plantations while other types of trade — especially direct trade between Western Africa and Europe — are often marginalised in scholarship. This article argues that the West African substance gum arabic played a vital role in the large-scale production of printed cottons and linens in Europe — one of the major areas of popular consumption at the time. Its unique qualities and the fact that it was available in large quantities made gum arabic from Senegal and Mauritania indispensable in producing high-quality prints in large numbers for a reasonable price. The article advances this argument by looking at Central instead of Western Europe, in order to illustrate how pervasive this substance was in the eighteenth century. Even regions far removed from the Atlantic — such as the South German city of Augsburg, in today's Bavaria — needed to find a way to access this Senegambian product in order to produce their popular textiles. The article thus seeks to contribute to a better understanding of Africa's role in the development of European textile industries and its contribution to consumption patterns by following a specific material from Western Africa to Central Europe — from Senegal to Augsburg.